Lymph node dissection in lung cancer surgery - Patel, Akshay J.; Bille, Andrea (Frontiers in Surgery, 2024)
Lung cancer, a leading cause of cancer-related death, often requires surgical resection for early-stage cases, with recent data supporting less invasive resections for tumors smaller than 2 cm. Central to resection is lymph node assessment, an area of controversy worldwide, compounded by advances in minimally invasive techniques. The review aims to assess current standards for lymph node assessment, recent data from the surgical era, and the immunobiological basis of how lymph node metastases impact patient outcomes. The British Thoracic Society guidelines recommend systematic nodal dissection during lung cancer resection, without specifying node removal or sampling. Historical data on mediastinal lymph node dissection (MLND) survival benefits are inconclusive, although proponents argue for lower recurrence rates. Recent trials such as ACOSOG Z0030 found no survival difference between MLND and nodal sampling, reinforcing the need for robust staging. While lobe-specific dissection strategies have been proposed, they currently lack consensus. JCOG1413 aims to compare the clinical benefits of lobe-specific and systematic dissection. TNM-9 staging revisions emphasize the prognostic significance of single-station N2 involvement. Robotic surgery shows promise, with trials such as RAVAL, which reported comparable outcomes to video-assisted thoracic surgery (VATS) and improved lymph node sampling. Immunobiological insights suggest preserving key immunological sites during lymphadenectomy, especially for patients receiving adjuvant immunotherapy. In conclusion, the standard lymph node resection strategy remains unsettled. The debate between systematic and selective dissection continues, with implications for staging accuracy and patient outcomes. As minimally invasive techniques evolve, robotic surgery emerges as an effective and low-risk approach to delivering optimal lymph node assessment.